Mechanisms of action of otilonium bromide (OB) in human cultured smooth muscle cells and rat colonic strips. Issue 12 (14th August 2013) - Martínez‐Cutillas, M.; Gil, V.; Gallego, D.; Mañé, N.; Martín, M. T.; Jiménez, M.
Abstract Background The pharmacological properties of otilonium bromide (OB) have been investigated using different experimental models, techniques, and conditions, and consequently, the results are not always easy to compare. The aim of the present work was to investigate the pharmacological properties of OB in human cultured colonic smooth muscle cells (HCSMCs), which is the main target of the drug 'in vivo'. Rat colonic strips were used to confirm the pharmacological properties. Methods Human cultured colonic smooth muscle cells were studied using the calcium imaging technique. Microelectrodes and muscle bath experiments were performed in rat colonic strips. Key Results Otilonium bromide (OB) concentration dependently inhibited nifedipine‐sensitive calcium transients induced by KCl (EC50 = 3.6 μM) and BayK8644 (EC50 = 4.0 μM). All the following experiments were performed in the presence of nifedipine. In HCSMC, carbachol‐induced calcium transients were inhibited by OB (EC50 = 8.4 μM). Carbachol evoked 1—a smooth muscle depolarization (10 mV) that was antagonized by 100 μM OB; and 2—a contraction that was inhibited by OB (EC50 = 13.0 μM). 'Non‐nitrergic (L‐NNA 1 mM) non‐purinergic (MRS2500 1 μM)' conditions were used to elicit endogenous excitatory responses. Electrical field stimulation caused 1—an atropine‐sensitive excitatory junction potential that was inhibited by OB (EC50 = 8.9 μM) and 2—an atropine‐sensitive contraction that was inhibited by OB (EC50 = 7.3 μM). In HCSMC, neurokinin A (NKA) and CaCl2 induced calcium transients that were inhibited by OB (NKA: EC50 = 11.7 μM; CaCl2: EC50 = 17.5 μM). Conclusions & Inferences Otilonium bromide causes inhibition of L‐/T‐type calcium channels, muscarinic, and tachykininergic responses that acting together explain the pharmacological properties of the compound.